2014
DOI: 10.1016/j.sjopt.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

External versus endonasal dacryocystorhinostomy in a specialized lacrimal surgery center

Abstract: Endonasal DCR surgery offers a very attractive alternative to the well established technique of external DCR surgery for the treatment of primary acquired nasolacrimal duct obstruction with equivalent success rates, shorter surgical time and higher patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 9 publications
0
36
0
2
Order By: Relevance
“…In this study, the author stated that they employed a packing, which was removed after one day in the patients. Gauba (17) reported no difference in either group in terms of postoperative bleeding. It was reported that there was no statistically significant difference between the two methods in terms of postoperative bleeding in a review of the studies comparing the two methods (18).…”
Section: Discussionmentioning
confidence: 92%
“…In this study, the author stated that they employed a packing, which was removed after one day in the patients. Gauba (17) reported no difference in either group in terms of postoperative bleeding. It was reported that there was no statistically significant difference between the two methods in terms of postoperative bleeding in a review of the studies comparing the two methods (18).…”
Section: Discussionmentioning
confidence: 92%
“…(18) Our results are comparable to Gauba who reported 18% cases of intraoperative haemorrhage in external DCR and 13% cases of intraoperative haemorrhage in endonasal DCR. (24) The bleeding was managed with local vasoconstrictive agents. The bleeding in case of external DCR can be from cutaneous vessels, branches of angular vessels, branches of ethmoidal vessels and from nasal mucosal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Nowadays, to this end, two basic techniques have been used as external and endonasal dacryocystorhinostomy. [6] External DCR was described by Toti in 1904 and various modifications of the original technique have been developed in subsequent years. [6] In various series, success rates of external DCR change between 70 and 100 percent.…”
mentioning
confidence: 99%
“…[6] External DCR was described by Toti in 1904 and various modifications of the original technique have been developed in subsequent years. [6] In various series, success rates of external DCR change between 70 and 100 percent. [7] Endonasal DCR was described by Caldwell in 1893 and then modified by West and Halle.…”
mentioning
confidence: 99%
See 1 more Smart Citation